Host plants and distribution records of lance flies (Diptera: Lonchaeidae) in São Paulo State, Brazil - Sousa, Ester Marques de (2021)
The knowledge of host plants, distribution and economic importance of Lonchaeidae is scarce in Latin America. We have recovered specimens of Lonchaeidae from most fruit samples containing specimens of Tephritidae. The compilation of information is essential to determine the diversity of species and the relationship with their hosts. In addition to the list of records based on early publications, we add unpublished data of Lonchaeids recovered from plant samples collected in the Instituto Biológico, São Paulo, Brazil. In total, 18 species of Lonchaeidae, belonging to the genera Dasiops, Lonchaea and Neosilba were registered in São Paulo, and associated with 111 host plant species and 27 botanical families. New records are listed and geographical distribution is available by specific maps.